Optimization of Supercapacitor Assisted Surge Absorber (SCASA) Technique: A New Approach to Improve Surge Endurance Using Air-Gapped Ferrite Cores - Sadeeshvara Udayanga Silva Thotabaddadurage; Nihal Kularatna; D. Alistair Steyn-Ross (Energies, 2021)
SCASA is a patented technique commercialized as a surge protector device (SPD) that adheres to UL-1449 test standards. Apart from the novel use of supercapacitors, SCASA design incorporates a coupled-inductor wound to a specially selected magnetic material of powdered-iron. In this study, we investigate the limitations of the present design under transient operation and elucidate ways to eliminate them with the use of air-gapped ferrite cores. In modelling the operation under 50 Hz AC and transient conditions, a permeance-based approach is used; in addition, non-ideal characteristics of the transformer core are emphasized and discussed with empirical validations. The experimental work was facilitated using a lightning surge simulator coupled with the 230 V AC utility mains; combinational surge-waveforms (6 kV/3 kA) defined by IEEE C62.41 standards were continuously injected into SPD prototypes during destructive testing. Such procedures substantiate the overall surge-endurance capabilities of the different core types under testing. With regard to optimizations, we validated a 95% depletion of a negative-surge effect that would otherwise pass to the load-end, and another 13–16% reduction of the clamping voltage verified the effectiveness of the methods undertaken. In conclusion, SCASA prototypes that utilized air-gapped cores revealed a greater surge endurance with improved load-end characteristics.